Analysis of Hydraulic Fracture Propagation Using a Mixed Mode and a Uniaxial Strain Model considering Geomechanical Properties in a Naturally Fractured Shale Reservoir. (23rd December 2020) - Jang, Youngho; Park, Gayoung; Kwon, Seoyoon; Min, Baehyun
Abstract : This study proposes a hydraulic fracture propagation model with a mixed mode comprising opening and sliding modes to describe a complex fracture network in a naturally fractured shale gas formation. We combine the fracture propagation model with the mixed mode and the uniaxial strain model with tectonic impacts to calculate the stress distribution using geomechanical properties. A discrete fracture network is employed to realize the fracture network composed of natural and hydraulic fractures. We compare the fracture propagation behaviours of three cases representing the Barnett, Marcellus, and Eagle Ford shale gas formations. Sensitivity analysis is performed to investigate the effects of the geomechanical properties of the reservoir on the sliding mode's contribution to the mixed mode. The numerical results highlight the significance of the mixed mode for the accurate assessment of fracture propagation behaviours in shale gas formations with high brittleness.